Radical Scavenging and Antioxidant Potential of Aqueous and Organic Extracts of Aerial Parts of Litchi chinensis Sonn. - U. Khan, Islam; N. Asghar, Muhammad; Iqbal, Sadaf; H. Bokhari, Tanveer; Khan, Zaheer-ud-Din (Asian Journal of Chemistry, 2010)
Extracts of medicinal plants have been reported to be very much effective in the control of chronic diseases due to their high antioxidant contents. Focus of the present study is the exploitation of safer and cheaper sources of the antioxidants based on the natural origin. Litichi chinensis Sonn. is used for its hypoglycemic activity in the traditional medicinal system of Indian subcontinent. The antioxidant activity of the aqueous and organic extracts of leaves, stem and fruit pulp of L. chinensis was investigated using 2,2'-azinobis(3-ethylbenzothiazoline- 6-sulpohonic acid) (ABTS) decolourization assay, the ferric reducing anti-oxidant power (FRAP) assay, 2.2'-diphenyl-1-picrylhydrazil (DPPH) assay, the total phenolic content (TPC) assay and the total antioxidant activity assay. Using the ABTS decolourization assay, L. chinensis extracts showed a wide range of antioxidant activity in terms of trolox equivalent antioxidant capacity (TEAC); from 5.64-0.126 mM for leaves of L. chinensis (LCL), from 4.12-0.23 mM for stem (LCS) and from 0.66-0.24 mM for fruit pulp of L. chinensis (LCPL). The total phenolic content assay exhibited 1.72, 1.46 and 1.41 mM gallic acid equivalents for ethyl acetate, aqueous (before partitioning) and aqueous (after partitioning) fractions of the stem respectively. The ferric reducing antioxidant power assay indicated high reducing power of leaves and stem of Litchi chinensis. Methanol, 1-butanol, aqueous and ethyl acetate fractions of all the parts of Litchi chinensis showed strong DPPH and peroxyl radicals scavenging activity. The results obtained in the present study demonstrated that all the pats studied are potential sources of natural antioxidants. Although the radical scavenging and inhibition of lipid peroxidation studies show usefulness of Litchi chinensis extracts in vitro conditions, yet verification of their in vivo activity and especially during disease conditions needs further experimentation.